Presença da gota citoplasmática e seus efeitos na morfometria, cromatina e motilidade espermática e identificação de genes candidatos à seleção de parâmetros seminais de suínos - Gaggini, Thais Schwarz (2017)
The main challenge of boars’ reproductive performance is related with two major lines of study that include the quality of the ejaculate/inseminating doses and boars fertility. In order to elucidate some points related to these lines, three studies were carried out with the aim of a) verify if the cytoplasmic droplet presence in sperm is associated with morphometric and chromatin characteristics; b) verify if reprobation of ejaculates due to high occurrence of distal cytoplasmic droplets interferes in spermatic movement parameters; c) investigate if there is a correlation among seminal parameters with specific genetic markers in boars. In the first study, 1,207 normal sperm and 725 sperm with cytoplasmic droplet were evaluated in relation to head morphometry and chromatin stability. Heads of sperm with cytoplasmic droplets were more elongated, laterally symmetrical, had higher percentage of decondensed chromatin and more heterogeneous chromatin than heads of normal sperm. These results indicate that morphological changes that do not occur directly on sperm head are associated with the conformation of the head and the structure of cell genetic material. In the second study it was compared parameters related to sperm movement in ejaculates considered approved (n=144) and rejected (n=25) exclusively due the high occurrence of distal cytoplasmic droplets on morphological exam. Sperm of rejected group presented lower velocity straight line, lower total and progressive motility than sperm of approved group. The reprobation due distal cytoplasmic droplet, which by several authors is considered without pathological significance, had a negative influence on sperm motion parameters. It suggests that reprobation for this cause should be considered in sperm morphology assessments. In the third research, a genomewide association study was performed with ejaculate volume, sperm concentration and total and progressive sperm motility, using 113 Duroc boars genotyped by Illumina PorcineSNP60 BeadChip. A total of 57 SNPs (single nucleotide polymorphism) windows that explained more than 1% of genetic variance were identified for ejaculate volume (22), sperm concentration (14), total (10) and progressive (11) motility. Thirteen genes of eight SNPs windows were considered candidates for those characteristics. Gene ABCC3 was related to volume, genes KCNA3, RBM15 and ITGB1 to sperm concentration, gene WRNIP1 to total motility, genes FAM189A2, C9orf135, FXN and FAM83D to progressive motility and genes HSD17B11 and HSD17B13 to total and progressive motility. The identification of possible candidate genes for the different seminal characteristics of boars can contribute to knowledge of the genetic background of swine production and also to improve the selection process of boars to be used in boar studs.